The Devonian-Cretaceous fossil record of "conchostracans" of Africa and their paleobiogeographic relationships with other Gondwanan faunas - Gallego, Oscar F.; Monferran, Mateo D.; Stigall, Alycia L.; Zacarias, Iracema A.; Hegna, Thomas A.; Jimenez, Victoria C.; Bittencourt, Jonathas S.; Li, Gang （李罡）; Barrios Calathaki, Hugo G. (Journal of African Earth Sciences, 2020)
The main objective of this work is to present a survey of the fossil record of "conchostracans", a group of continental (also occasionally from brackish and marine sequences) fossil invertebrates, recorded from Africa, to explore relationships among these taxa and those recorded from other paleocontinents, and to assess the potential for the African "conchostracan" records to provide insight on paleobiogeographic connections within Gondwana. This work is focused on "conchostracans" (laevicaudatans, spinicaudatans and cyclestheriids), because "conchostracans" are one of the most widely documented groups in the Phanerozoic continental sequences. A clear signal of taxonomic change is recovered within the African fauna. Leaiids, lioestheriids and palaeolimnadiids characterize African Paleozoic-Triassic strata, whereas afrograptids, fushunograptids and palaeolimnadiopseids characterize African Mesozoic strata. The relationship among African and other Gondwanan taxa is considered, and the potential for "conchostracans" as paleobiogeographic indicators is evaluated. Biogeographic analysis is based on the compiled data about the African "conchostacans" fossil record with specific consideration of some emblematic groups (Leaiidae, Paleolimnadidae, Vertexiinae, and Afrograptidae). Key dispersal pathways may have operated. During the Devonian to Triassic, records suggest four different faunal interchanges between Africa and Australia, Europe, South America, and India. During the Jurassic to Cretaceous, records suggest five different faunal interchanges between Africa and South America, Europe, Asia, India and Antarctica marked by different emblematic taxa.